The Revision Rhinoplasty Consult: The Art of Managing Expectations. - Marcus, Benjamin C. (Facial Plastic Surgery, 2018)
Rhinoplasty is widely acknowledged to be a challenging operation. The success of the operation has long been measured in anecdotal ways. As the surgeon—do I think the outcome is good? Does the patient tell me they are happy? At hand is an obvious issue with patients sometimes not returning to their original doctor. Other times they may have minor concerns that take minimal effort to correct. Does that constitute a revision? In most circles, the ultimate definition of revision rhinoplasty is a return to surgery with the intent to correct a functional or aesthetic concern that arose after the original procedure.
Keywords: rhinoplasty; revision rhinoplasty